The love for the poor neighbour: in memory of her (Matthew 26:6-13) - A. G. van Aarde (Acta Theologica)
This article explores whether the Jesus saying in Matthew 26:11 contradicts the Jesus tradition about caring for the poor. Bultmann’s understanding of the love commandment provides a key to understanding this perceived paradox. On the one hand, in Matthew 19:21, Jesus says that to love one’s neighbour as required by the Decalogue means, in practice, to dispose of all riches and give the money to the poor. On the other hand, in Matthew 26:6-14, Jesus pardons the woman who anointed him with precious oil in anticipation of his burial rather than selling the oil and giving the money to the poor. The article argues that the Matthean Jesus did not contradict himself. Bultmann’s insight into the dialectical dissociation between Christian ethics and Stoic ethics supports the coherence in Jesus’ view on caring for the poor.